Achieving quality comfort care in nursing homes and long term care units through ambient assisted living (AAL) environments - Page, Robert; Richardson, Anthony S.; Coppola, Jean (International Journal of Interdisciplinary Research, 2016)
Nursing home administrators are caught in a "perfect storm" of rapidly increasing health care costs, decreasing reimbursement, and increasing competition. This paper documents how these pressures create cascading misalignments resulting in compromises of the quality of comfort care. These problems are inevitable, given the increase in unfunded mandates, where performance evaluation is decoupled from actual performance. Ambient technologies are explored as a means of tracking actual care versus reported care. Independent quality of care tracking and documentation of ambient data, coupled with best practice research and rewards, are explored to promote quality care as a marketing advantage. Implications are discussed.
Keywords: dept.bis; peer-reviewed

Change Requires Change! Information Technology, Student Preparedness and Industry Collaboration: Supporting the Bridging Process between Education and Training with Innovative Solutions - O'Sullivan, Jill (Journal of Systemics, Cybernetics and Informatics, 2016)
This paper, Change Requires Change: will relate that bridging the gap between education: of what we teach and training: of what industry looks for in prepared skills for students, needs to be relevant to today’s situations. We need to re-evaluate traditional industry academic partnerships which have been relatively successful including; internships, work-study programs, curriculum advisory boards, guest lectures and capstone courses, to identify gaps and opportunities for what is needed to support our future. Do we want to continue with the status-quo or enhance education? Should we be cognizant of emerging trends? What could be the implications on changing academic-industry partnerships? How can we improve? This paper proposes several new approaches to academics and industry practitioner’s towards greater successful collaborations towards student preparation.
Keywords: dept.bis; peer-reviewed